INTELLECTUAL CAPITAL DISCLOSURE DAN KAPITALISASI PASAR DI INDONESIA - Soelistijono Boedi (University of Merdeka Malang, 2010)
This study examined the differences of Intellectual Capital Disclosure (ICD) betweennew industry and old industry, therefore influence of ICD on market capitalizationcontinuing research by Abdolmohammadi (2005), as for becoming object from this researchwas all industry listed in Jakarta Stock Exchange (JSX). This research represented the empiricaltest which used purposive sampling techniques in data collection. Data were collectedusing a secondary data of 65 from industry 2003 to 2007. Data analysis used regression. Theresults of hypothesis examination indicated that from five hypothesis raised, there were fouraccepted hypothesis. Accepted hypothesis were hypothesis 1 (there were significant differencesbetween new industry and old industry of ICD on annual report), hypothesis 3 (therewas no significant influence in book value on market capitalization) and hypothesis 4 (therewas a significant influence in ROA Difference on market capitalization). There was one hypothesisthat was no correlation, it was hypothesis 2 (there was no significant influencebetween ICD on market capitalization). From this result, it could be concluded that intellectualcapital disclousure had no influence on capitalization market value therefore intellectualcapital disclosure had no difference between new industri and old industri.